2022
DOI: 10.2188/jea.je20200305
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Causal Roles of Circulating Remnant Lipid Profile on Cardiovascular and Cerebrovascular Diseases: Mendelian Randomization Study

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Due to its atherogenic properties, RC can contribute to atherosclerosis in both the carotid artery [ 21 ] and arterioles in the brain. A Mendelian randomization study confirmed the causal relationship of remnant lipoprotein-associated genes and ischemic stroke [ 22 ]. Prospective cohort studies on symptomatic intracranial atherosclerotic stenosis and ischemic stroke indicated that RC causes cerebral hypoperfusion [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its atherogenic properties, RC can contribute to atherosclerosis in both the carotid artery [ 21 ] and arterioles in the brain. A Mendelian randomization study confirmed the causal relationship of remnant lipoprotein-associated genes and ischemic stroke [ 22 ]. Prospective cohort studies on symptomatic intracranial atherosclerotic stenosis and ischemic stroke indicated that RC causes cerebral hypoperfusion [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…F-statistics were applied to quantify the strength of the selected instruments. In general, the Fstatistic > 10 would be considered strong as previous research [19].…”
Section: Genetic Instrumental Variables (Ivs)mentioning
confidence: 70%
“…Due to its atherogenic properties, RC can contribute to atherosclerosis in both the carotid artery [21] and arterioles in the brain. A Mendelian randomization study con rmed the causal relationship of remnant lipoprotein-associated genes and ischaemic stroke [22]. Prospective cohort studies on symptomatic intracranial atherosclerotic stenosis and ischaemic stroke indicated that RC causes cerebral hypoperfusion [23].…”
Section: Discussionmentioning
confidence: 99%